2007
DOI: 10.1103/physrevlett.98.134101
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Bursting through Homoclinic Spike Adding in a Neuron Model

Abstract: The origin of spike adding in bursting activity is studied in a reduced model of the leech heart interneuron. We show that, as the activation kinetics of the slow potassium current are shifted towards depolarized membrane potential values, the bursting phase accommodates incrementally more spikes into the train. This phenomenon is attested to be caused by the homoclinic bifurcations of a saddle periodic orbit setting the threshold between the tonic spiking and quiescent phases of the bursting. The fundamentals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 27 publications
1
74
0
Order By: Relevance
“…A novel practical method for constructing a complete family of onto mappings for membrane potentials of slow-fast neuronal models was proposed in Channell et al (2007a, b) following an idea suggested originally in Shilnikov (1993). Using this approach we have studied spike adding transitions in a leech heart interneuron model and revealed that this phenomenon is associated with homoclinic bifurcations of a saddle periodic orbit (Channell et al 2007a). …”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…A novel practical method for constructing a complete family of onto mappings for membrane potentials of slow-fast neuronal models was proposed in Channell et al (2007a, b) following an idea suggested originally in Shilnikov (1993). Using this approach we have studied spike adding transitions in a leech heart interneuron model and revealed that this phenomenon is associated with homoclinic bifurcations of a saddle periodic orbit (Channell et al 2007a). …”
Section: Introductionmentioning
confidence: 96%
“…They work exceptionally well in the most low-order mathematical and realistic models far from bifurcations of bursting. However, at activity transitions, the bursting behavior can become drastically complex and even chaotic (Terman 1991(Terman , 1992Holden and Fan 1992;Wang 1993;Belykh et al 2000;Feudel et al 2000;Deng and Hines 2002;Elson et al 2002;Shilnikov and Cymbalyuk 2004;Cymbalyuk and Shilnikov 2005;Channell et al 2007a) due to reciprocal interaction between the slow and fast dynamics, which lead to the emergence of novel dynamical phenomena and bifurcations that can only occur in the entire system. Recently a novel method which identifies effective low-dimensional local models to study the transition between tonic and bursting regimes was developed in Clewley et al (2009).…”
Section: Introductionmentioning
confidence: 98%
“…Starting from that seminal mathematical model, a lot of variant models describing different kinds of neuron cells in numerous animals have been proposed in the literature. For instance, a reduced model [2][3][4] of the bursting of leech heart neuron is specified by the following three equations derived through the Hodgkin-Huxley gated variable formalism:…”
mentioning
confidence: 99%
“…A functionally driven reduction of all currents involved in this feedback could be expected to allow meaningful quantification of the degree to which release plays a role in comparison to escape. It may also facilitate phase plane and bifurcation analysis of the hybrid dynamics for these feedback loops, for instance along the lines of [1,11,19,24,26].…”
Section: Insight Into the Escape-release Mechanismmentioning
confidence: 99%